Interleukin‐31: its role in canine pruritus and naturally occurring canine atopic dermatitis. Issue 1 (19th January 2013) - Gonzales, Andrea J.; Humphrey, William R.; Messamore, James E.; Fleck, Timothy J.; Fici, Gregory J.; Shelly, John A.; Teel, Janet F.; Bammert, Gary F.; Dunham, Steven A.; Fuller, Troy E.; McCall, Robert B.
<x xml:space="preserve">Abstract</x> Background – Interleukin‐31 (IL‐31) is a member of the gp130/interleukin‐6 cytokine family that is produced by cell types such as T helper 2 lymphocytes and cutaneous lymphocyte antigen positive skin homing T cells. When overexpressed in transgenic mice, IL‐31 induces severe pruritus, alopecia and skin lesions. In humans, IL‐31 serum levels correlate with the severity of atopic dermatitis in adults and children. Hypothesis/Objective – To determine the role of IL‐31 in canine pruritus and naturally occurring canine atopic dermatitis (AD). Animals – Purpose‐bred beagle dogs were used for laboratory studies. Serum samples were obtained from laboratory animals, nondiseased client‐owned dogs and client‐owned dogs diagnosed with naturally occurring AD. Methods – Purpose‐bred beagle dogs were administered canine interleukin‐31 (cIL‐31) via several routes (intravenous, subcutaneous or intradermal), and pruritic behaviour was observed/quantified via video monitoring. Quantitative immunoassay techniques were employed to measure serum levels of cIL‐31 in dogs. Results – Injection of cIL‐31 into laboratory beagle dogs caused transient episodes of pruritic behaviour regardless of the route of administration. When evaluated over a 2 h period, dogs receiving cIL‐31 exhibited a significant increase in pruritic behaviour compared with dogs that received placebo. In addition, cIL‐31 levels were detectable in 57% of dogs with naturally occurring AD (≥13 pg/mL) but were below limits of quantification (<13 pg/mL) in normal, nondiseased laboratory or client‐owned animals. Conclusions – Canine IL‐31 induced pruritic behaviours in dogs. Canine IL‐31 was detected in the majority of dogs with naturally occurring AD, suggesting that this cytokine may play an important role in pruritic allergic skin conditions, such as atopic dermatitis, in this species.